Marketing and marketing activities: current state of the problem - Maksymiuk, Yu. (Ways to Improve Construction Efficiency, 2023)
The article analyzes the modern problems of marketing and marketing activity. Relying on classic, well-known and recent scientific studies in this area, a review of literary sources, both domestic and foreign specialists in this area, was performed. It examines what strategies and approaches in marketing activities are relevant in today’s market, including the use of digital technologies, personalization, environmental responsibility and other factors. The main challenges and problems faced by companies in the field of marketing are analyzed, such as increased competition, changes in consumer behavior, extraordinary circumstances arising from the pandemic, etc. It highlights what opportunities open up for marketing thanks to modern technologies and trends, and what strategies can help companies solve complex tasks. It was concluded that marketing is a discipline that largely integrates the work of economic theory and management and can be used for the development of the construction industry. The roots of marketing come from microeconomics, and the classical theory of marketing is among the main sciences about the enterprise, dealing with practical aspects of business functioning. The essence of marketing orientation boils down to the conduct of such activities, which, on the one hand, are able to ensure the realization of the company’s goals and profit, and on the other hand, to satisfy the needs of partners and maintain good relations with them. Researching the current state and problems of marketing is an urgent task for practitioners and researchers focused on successful business. The research can be a theoretical basis for construction companies of various sizes and forms of ownership, as well as development enterprises when forming a system of marketing measures for the development of the company, entering new markets and choosing new tools that will contribute to further development.